Ativação da caspase-11 durante a infecção por Plasmodium Chabaudi - Natália Martinez de Araújo (2015)
Malaria is an infectious disease caused by the parasite Plasmodium, which is transmitted through a bite from infected Anopheles mosquitoes. The main features of malaria disease are high parasitemia and systemic production of cytokines like IL-1 and TNF, which cause fever and chills. Pyrogenic and inflammatory cytokines production is initiated by phagocytic monocytes, which recognize malaria toxins like glycosylphosphatidylinositol (GPI) and hemozoin. These toxins are agonists of surface receptors and cytoplasmic receptors such as the NOD receptors (NLRs). The inflammasome that is composed by NLRs is important for caspase-1 activation, which in turn cleaves pro-IL-1 beta into its active form. Recently it was described non-canonical pathway caspase-1 activation by inflammasome, which is dependent of capase-11. We demonstrated that during P. chabaudi infection, the caspase-11 is induced and activated, but caspase-11 wasnt important to caspase-1 activation. The infected animals are hypersensitive, after lipopolysaccharide (LPS) challenge. This occurs because the infected and challenged animals show high levels of IL-1 and died a few hours later. However, we showed that caspase-11 can be important to IL-1 levels in infected animals that were challenged with LPS. Moreover, the infected animals caspase-11 knockout showed great number of survivals than wild type mice, after LPS challenge.